A participação de diferentes atores no processo de atualização do currículo da cidade : matemática nos anos iniciais - Santos, Bianca Freire dos (2020)
The Sao Paulo Municipal Education Office, during the year of 2017, accomplished the third version of the National Common Curriculum Base, along with other materials already produced by its own network. This update had its process finished in December of 2017, released date of the entitled document called "City's Curriculum". According to the documents from the Sao Paulo Municipal Education Office, the proposal was assembled with the participation of teachers' network, professionals responsible for the teachers' formation, along with pedagogical and technician advisors. Therefore, this work intends to analyze the participation of these different artists involved during the building process of the City's Curriculum - Mathematics, for the initial years, as from the documental analysis and the semi structured interview. For our curriculum discussion, there were contributions from Sacristán, Pacheco, Palanch, Pires. From our analysis, the results reveal that the proposal's quest contemplate every network participation, throughout different motions that brought different possibilities and contributions.